Assessment of dehydration using body mass changes of elite marathoners in the tropics - Ren Tan, X.; Chiet Low, I. C.; Byrne, C.; Wang, R.; Wei Lee, J. K. (Journal of Science and Medicine in Sport, 2021)
Objectives: The ACSM recommends drinking to avoid loss of body mass >2% during exercise to avert compromised performance. Our study aimed to assess the level of dehydration in elite runners following a city marathon in a tropical environment. Design: Prospective cohort design. Methods: Twelve elite runners (6 males, 6 females; age 24-41 y) had body mass measured to the nearest 0.01 kg in their race attire immediately before and after the 2017 Standard Chartered Singapore Marathon 2017. Body mass change was corrected for respiratory water loss, gas exchange, and sweat retained in clothing, and expressed as % of pre-race mass (i.e. % dehydration). Results: Data are expressed as means ± SD (range). Dry bulb temperature and humidity were 27.9 ± 0.1 °C (27.4-28.3 °C) and 79 ± 2% (73-82%). Finish time was 155 ± 10 min (143-172 min). Male runners finishing positions ranged from 2-12 out of 7627 finishers, whilst female runners placed 1-8 out of 1754 finishers. Body mass change (loss) and % dehydration for all runners were 2.5 ± 0.5 kg (1.8-3.5 kg) and 4.6 ± 0.9% (3.6-6.8%). Male runners experienced body mass loss of 2.8 ± 0.5 kg and 4.9 ± 1.2% while females experienced body mass loss of 2.1 ± 0.2 kg and 4.3 ± 0.6%. Conclusions: Despite experiencing dehydration (4.6% body mass loss) two-fold higher than current fluid replacement guidelines recommend (=2%), elite male and female runners performed successfully and without medical complication in a hot weather marathon.